Exploitation of Antibiofilm Substances by Endophytic Bacteria of Renggak Fruit (Amomum dealbatum) Against Staphylococcus aureus, the Cause of Nosocomial Infections - Hijriani, Baiq Isti; Atfal, Bustanul; Kamila, Natasya Cahya (Jurnal Sain Veteriner, 2026)
Nosocomial infections can be caused by biofilm-forming microorganisms. The ability to form biofilms results in persistent, recurrent, and 100-1000 times more resistant to antibiotics. One of the biofilm-forming bacteria is Staphylococcus aureus. The renggak plant (Amomum dealbatum Roxb.) which contains alkaloids, steroids, flavonoids, terpenoids, tannins, and saponins is known to play a role in inhibiting bacterial biofilm formation. This study used an in vitro experimental design aimed to analyzing the antibiofilm activity of endophytic bacteria against Staphylococcus aureus using the plate tissue culture method. The results obtained five endophytic bacterial isolates, including BI1, BI2, BI3, BI4, and BI5. The percentage of biofilm inhibitory activity by cell-free supernatants of endophytic bacteria was 35%, 0%, 37%, 44%, and 39%, respectively, with a positive control was 42%. Meanwhile, the biofilm revealing activity was 39%, 42%, 41%, 38%, and 36%, respectively, with a positive control was 56%. The results of the One Way ANOVA statistical test obtained a significance result of 0.000 (p<0.005), which means there was a significant difference between the treatment groups in the antibiofilm test. The conclusion is the cell-free supernatant of endophytic bacteria from renggak fruit has inhibitory and degradation activity against Staphylococcus aureus bacterial biofilms.